A typology for exploring the quality of explanations for non-compliance with UK corporate governance regulations. Issue 1 (March 2015) - Shrives, Philip J.; Brennan, Niamh M.
Abstract Companies not complying with the UK Corporate Governance Code are required to provide explanations for non-compliance. This is the capstone of the 'comply-or-explain' system. There are no regulations about the content of those explanations, leaving shareholders and others to judge their appropriateness. The study develops a typology to assess the quality of corporate governance explanations for non-compliance of UK FTSE 350 companies based on seven quality characteristics. Code breaches generating the non-compliance explanations for analysis are identified for two accounting periods (2004/5 and 2011/12) relating to the 2003 and 2010 Codes (data for 2011/12 in brackets). There were 204 (125) non-compliant companies, 537 (253) Code breaches and 438 (208) explanations for non-compliance, an average of 2.6 (2.0) Code breaches and 2.2 (1.7) explanations per non-compliant company. Although compliance increased over the period examined, explanations were found to be of variable quality. Results suggest that companies need to improve the quality of their explanations if they are to be useful to users, notably location, complexity and specificity of explanations. There are also important questions raised about the work of auditors and their apparent silence. Companies are being encouraged to move towards compliance. We argue that this is against the 'comply-or-explain' philosophy which accepts that 'one size does not fit all.' Better quality of explanation is more important than compliance and thus companies may be unwittingly heading in the wrong direction.